Sexual Violence in Higher Education, Policies in Indonesia and India - Sukeni, Dewi Setyowati; Bhanu Prakash (Universitas Muhammadiyah Surabaya, 2023)
The phenomenon of sexual violence in college is a serious concern of the Ministry of Education and Culture, and in order to prevent and handle the occurrence of sexual violence in college, the Minister of Education and Culture Regulation Number 30 Year 2021 concerning Prevention and Handling of Sexual Violence in Higher Education is issued (hereinafter referred to as Permendikbud 30 / 2021) which was promulgated on September 30, 2021. The enactment of Permendikbud 30 / 2021 raises pros and cons in the community such as the enactment of provisions regarding